Simultaneous acoustic navigation of multiple AUVs - Aníbal Matos (2006)
Although the simultaneous use of multiple AUVs in some mission scenarios is advantageous when compared with single AUV operations, it poses some challenging questions regarding the coordinated control and navigation of multiple vehicle operations. This paper addresses the simultaneous navigation of multiple vehicles using the same acoustic network. We propose a configuration for a long baseline acoustic network that allows each vehicle to determine its position as well as the positions of all the other vehicles using the same network. The proposed mode of operation minimizes the number of additional signal exchanges. Furthermore, this is accomplished without the need of any communication link between the vehicles.